Noninvasive Cerebral Oximetry during Endovascular Therapy for Acute Ischemic Stroke: An Observational Study. Issue 11 (November 2015) - Hametner, Christian; Stanarcevic, Predrag; Stampfl, Sibylle; Rohde, Stefan; Veltkamp, Roland; Bösel, Julian
Implementing endovascular stroke care often impedes neurologic assessment in patients who need sedation or general anesthesia. Cerebral near-infrared spectroscopy (NIRS) may help physicians monitor cerebral tissue viability, but data in hyperacute stroke patients receiving endovascular treatment are sparse. In this observational study, the NIRS index regional oxygen saturation (rSO2 ) was measured noninvasively before, during, and after endovascular therapy via bilateral forehead NIRS optodes. During the study period, 63 patients were monitored with NIRS; 43 qualified for analysis. Before recanalization, 10 distinct rSO2 decreases occurred in 11 patients with respect to time to intubation. During recanalization, two kinds of unilateral rSO2 changes occurred in the affected hemisphere: small peaks throughout the treatment ( n = 14, 32.6%) and sustained increases immediately after recanalization ( n = 2, 4.7%). Lower area under the curve 10% below baseline was associated with better reperfusion status (thrombolysis in cerebral infarction ≥ 2b, P = 0.009). At the end of the intervention, lower interhemispheric rSO2 difference predicted death within 90 days ( P = 0.037). After the intervention, higher rSO2 variability predicted poor outcome (modified Rankin scale > 3, P = 0.032). Our findings suggest that bi-channel rSO2 -NIRS has potential for guiding neuroanesthesia and predicting outcome. To better monitor local revascularization, an improved stroke-specific set-up in future studies is necessary.